Integrated water resources management in Khartoum, Sudan: A feasibility study with a focus on Islamic principles / Rasha Mohammed Abdalall Mohammed Nour - Rasha Mohammed Abdalall, Mohammed Nour (2018)
Integrated Water Resources Management (IWRM) is a promising concept which is widely used as means for poverty alleviation, enhance the provision of drinking water and to improve the public heath situation for different community. Khartoum state suffering from population increases and urban expansion which, result in water shortage, water pollution and water related disease. The issue of water problems in Sudan is mainly attributing to poor water resources management rather than water scarcity. This research conducted to explore the feasibility of implementation of IWRM among Khartoum population Sudan, through the identification of the different factors that have potential to enhance and impede the IWRM implementation. The interview, documentation sources and public survey technique was conducted to collect related data. The data was analyzed by using thematic analysis, SWOT analysis as well as simple statistical analysis. The result of analysis showed that most important factors that impact the IWRM application are the institutional capacity of the water sector, water legislation as well as the community participation. It also indicates that the Muslims community in Khartoum has a high potential to improve the IWRM implementation. This research will contribute to the current status of the IWRM in Khartoum in determining the most important steps towards implementing an appropriate action plan for successful IWRM, where now Khartoum government in the pre-stage of IWRM implementation.